Blocking heterochromatin spreading constrains cohesin binding at a yeast heterochromatic locus - Paul M. Kraycer; Marc R. Gartenberg (PLoS ONE, 2026)
Cohesin mediates central features of chromosome architecture. The protein complex governs sister chromatid cohesion and organizes genomes into loops and domains. In budding yeast, cohesin accumulates at discrete sites on chromosome arms, as well as at domains of heterochromatin. The molecular basis for the distribution at these sites is not yet resolved, although the heterochromatin protein Sir2 has been implicated. If cohesin were to bind a recurring feature of heterochromatin, then size of the cohesin domain would match the size of the heterochromatin domain. To test this hypothesis, the span of heterochromatin at the HMR silent mating-type locus was truncated with artificial barrier elements built from bacterial DNA binding proteins. We found that the most effective barrier reduced the footprint of Sir3 and Smc3, representative components of yeast heterochromatin and cohesin. These results show that reducing the span of heterochromatin at HMR constrains the size of the cohesin bound domain.